Regional differences in general practitioners' behaviours regarding influenza vaccination: a cross-sectional study - Jonathan Arlt; Kristina Flaegel; Katja Goetz; Jost Steinhaeuser (BMC, 2021)
Abstract Background The World Health Organization recommends vaccination rates of 75% against seasonal influenza for patients over 65 years old. In the 2013/2014 season, the German vaccination rates ranged between 14 and 65%. This study aimed to compare the attitudes, personal characteristics and vaccination behaviours of general practitioners (GPs) in regions with high and low vaccination rates in Germany. Methods In May 2016, a questionnaire was sent to 1594 GPs practising in 16 districts with the highest and the lowest vaccination rates in Western and Eastern Germany as described by the Central Research Institute of Ambulatory Health Care in Germany for the 2013/2014 season. Descriptive statistics and multiple regression analyses were computed to identify potential factors associated with high vaccination rates. Results A total response rate of 32% (515/1594 participants) was observed in the study. GPs reported their attitudes towards vaccination in general and vaccination against influenza as mostly 'very positive' (80%, n = 352 and 65%, n = 288, respectively). GPs practising in regions with low vaccination rates reported their attitudes towards vaccinations in general (p = 0.004) and towards influenza vaccination (p = 0.001) more negatively than their colleagues from regions with high vaccination rates. Multiple logistic regression identified an increasing influence of year-dependent changing efficiency on GPs' influenza rates as the strongest factor for predicting GPs from highly vaccinating regions (OR = 4.31 [1.12-16.60]), followed by the patient's vaccination refusal despite GP advice due to already receiving a vaccination from another physician (OR = 3.20 [1.89-5.43]) and vaccination information gathering through medical colleagues (OR = 2.26 [1.19-4.29]). Conclusions The results of this study suggest a correlation between GPs' attitudes and regional vaccination rates. Beneath GPs' individual attitudes, the regional attitude patterns of patients, colleagues and medical assistants surrounding those GPs seem decisive and should be integrated into future campaigns to increase vaccination rates at a regional level.